Response analysis on synthesized aluminium-scandium metal matrix composite using unconventional machining processes. (2020) - Pritima, D.; Vairamuthu, J.; Gopi Krishnan, P.; Marichamy, S.; Stalin, B.; Sheeba Rani, S.
Abstract: The research work and applications of aluminium based Metal Matrix Composite (MMC) has been increased. It has more attractive material properties like strength, ductility, corrosion and wear resistance. The current work reports the Titanium Carbide (TiC) and Vanadium Carbide (VC) reinforced aluminium scandium MMC is formulated through metallurgy technique. The synthesized MMC is under various materials testing for evaluating the properties. After addition of TiC and VC, the material properties have been increased. Hence, Unconventional machining techniques such as Spark Erosion or Electrical Discharge Machining (EDM), Abrasive Water Jet Machining (AWJM) and Laser Beam Machining (LBM) have been carried out. In each machining processes, the influential parameter effect is determined through the Analysis of Variance (ANOVA). The orthogonal array (L9 ) based Taguchi approach is employed to find the optimal parameter for Material Deletion Rate (MDR).